2019
DOI: 10.1017/s0033291719001077
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and psychosis: revisiting a nineteenth century study of ‘Indian Hemp and Insanity’ in Colonial British India

Abstract: BackgroundIn nineteenth-century British India, concern regarding large numbers of asylum patients with ‘Indian Hemp Insanity’ led to establishment of the Indian Hemp Drugs Commission. The exotic cannabis plant was widely used in pharmacopeia and a source of government revenue. The Commission was tasked with determining the public health risks of cannabis use, particularly mental illness. This analysis of the Commission report seeks to highlight the status of 1892 cannabis research and compare it with current e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The association between cannabis use and psychosis has been recognised for centuries ( Ayonrinde, 2020 ), with substantial and increasing evidence for a causal relationship ( Vaucher et al, 2018 ). There is a dose-response relationship, with the greatest risks of psychosis observed in daily users ( Marconi et al, 2016 , Robinson et al, 2022 ) and those who use high-potency cannabis (i.e.…”
Section: Mechanistic Pathwaysmentioning
confidence: 99%
“…The association between cannabis use and psychosis has been recognised for centuries ( Ayonrinde, 2020 ), with substantial and increasing evidence for a causal relationship ( Vaucher et al, 2018 ). There is a dose-response relationship, with the greatest risks of psychosis observed in daily users ( Marconi et al, 2016 , Robinson et al, 2022 ) and those who use high-potency cannabis (i.e.…”
Section: Mechanistic Pathwaysmentioning
confidence: 99%
“…It concluded that only very heavy use of cannabis led to drastic physical, mental, and moral effects, not intermittent use. 27, 28 The following decades saw an unrestricted increase in cannabis cultivation and use, which peaked during the 1960s in India and Nepal. 29 However, India passed the Narcotic Drugs and Psychotropic Substances Act in 1985, effectively banning the cultivation, production, and consumption of cannabis along with 70 other narcotic and psychotropic drugs.…”
Section: Historical and Sociocultural Underpinnings Of Cannabis Use I...mentioning
confidence: 99%
“…Cannabis is a substance that has been consumed in various formulations and for different purposes over many centuries. 1 There is a changing legislative landscape from decriminalization to the legalization of cannabis, primarily for medical purposes, and in some jurisdictions for recreational use. Despite the rising enthusiasm for cannabis use as a panacea for varied conditions, there are conflicting views and relatively few high-quality studies regarding the health benefits and harms of more liberal cannabis consumption.…”
Section: Introductionmentioning
confidence: 99%